The Legal Safeguards For Buyers of Land Acquired Through Debt Settlement (Study of Decision Number 12/Pdt.G/2018/PN.Btl) - Ramdhan, Syaffi' Rangga Raditya; Rachmi Sulistyarini; Dyah Ayu Wisnuwardhani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
Legal protection for good-faith land buyers is a fundamental aspect in maintaining the balance between justice, legal certainty, and benefit in the Indonesian civil law system. Problems often arise when the land being traded is previously involved in a debt-to-credit relationship, thus giving rise to potential disputes between creditors and buyers. This article aims to analyze the forms of legal protection for good-faith buyers based on the provisions of the Civil Code, the Basic Agrarian Law, and various Supreme Court jurisprudential decisions. The analysis results show that good-faith buyers receive legal protection in three forms: preventive, repressive, and normative. Preventive protection is realized through land administration mechanisms such as the preparation of a sale and purchase deed by a Land Deed Official (PPAT) and land registration at the land office. Repressive protection is provided through a court decision rejecting a third-party lawsuit if it is proven that the buyer has acted in good faith. Meanwhile, normative protection stems from the principles of good faith, the principle of legal certainty, and the doctrine of justice applicable in Indonesian civil law. Thus, the existence of this legal protection not only guarantees ownership rights for buyers in good faith, but also strengthens public trust in the national land law and governance system.